The types of tumor infiltrating lymphocytes are valuable for the diagnosis and prognosis of breast cancer - Sun, Ying; Zhang, Chunyan (Frontiers in Genetics, 2022)
This study aimed at constructing a dIRS system and a pIRS system for breast cancer (BC). GSE65194, GSE29044, GSE42568, and GSE20685 from Gene Expression Omnibus (GEO) database were extracted. The TCGA dataset was used as training set to build the dIRS system by using EPIC tool, SVM-RFE and RF-OOB algorithms. Besides, the pIRS system and the nomogram survival model were established separately using penalized and rms packages. The datasets from GEO were used as validation datasets for dIRS system and pIRS system. A dIRS system (involving B cells, CD8+T cells, endothelial cells, NK cells, and other cells) and a pIRS system (involving B cells, endothelial cells, macrophages, NK cells, and other cells) were constructed separately. The AUROC of dIRS for the training set and validation sets were 0.963, 0.862, 0.766 and 0.843, respectively. Kaplan-Meier analysis demonstrated that the survival rate of low pIRS group was significantly higher than that of high pIRS group (P < 0.05). Based on age, stage and the pIRS values, the nomogram survival model was built. The c-indexes were higher than 0.7000. The dIRS system and the pIRS system might be critical for the diagnosis and prognosis of BC patients.